Acoustics and psychoacoustics - Howard, David M. 1956-; Angus, Jamie (Routledge, 2017)
The acoustics of a space can have a real impact on the sounds you create and capture. Acoustics and Psychoacoustics , Fifth Edition provides supportive tools and exercises to help you understand how music sounds and behaves in different spaces, whether during a performance or a recording, when planning a control room or listening space, and how it is perceived by performers, listeners, and recording engineers. With their clear and simple style, Howard and Angus cover both theory and practice by addressing the science of sound engineering and music production, the acoustics of musical instruments, the ways in which we hear musical sounds, the underlying principles of sound processing, and the application of these concepts to music spaces to create professional sound. This new edition is fully revised to reflect new psychoacoustic information related to timbre and temporal perception, including an updated discussion of vocal fold vibration principles, samples of recent acoustic treatments, and a description of variable acoustics in spaces, as well as coverage of the environment's effect on production listening, sonification, and other topics. Devoted to the teaching of musical understanding, an accompanying website (www.routledge.com/cw/howard) features various audio clips, tutorial sheets, questions and answers, and trainings that will take your perception of sound to the next level. This book will help you: Gain a basic grounding in acoustics and psychoacoustics with respect to music audio technology systems Incorporate knowledge of psychoacoustics in future music technology system designs as appropriate Understand how we hear pitch, loudness, and timbre Learn to influence the acoustics of an enclosed space through designed physical modifications.
Includes bibliographical references and index. - Description based on print version record
Keywords: Music -- Acoustics and physics; Psychoacoustics; Musique; Acoustique et physique; Psychoacoustique; Music; Acoustics and physics